Миоценовые птицы Западного Причерноморья УССР - Уманская, А.С. (Вестник зоологии, 1981)
Three new bird species (Gavia paradoxa, Falco medius, Picus peregrinabundus) are describedfromthe Late Miocenedeposits i nthe Western Black Sea territory of the Ukrainian SSR. Relations of the fossil forms with recent and other fossil forms are determined.